2017
DOI: 10.15252/embj.201797845
|View full text |Cite
|
Sign up to set email alerts
|

Live and let die: ZBP1 senses viral and cellular RNAs to trigger necroptosis

Abstract: Necroptosis is a programmed form of inflammatory cell death involved in various pathologies, such as viral infections. In two new papers published in The EMBO Journal and EMBO Reports, Z‐DNA binding protein 1 (ZBP1) is now shown to sense RNAs during viral infection or after caspase inhibition and activate necroptosis. This may suggest that Z‐RNAs are molecular patterns for activation of necroptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is shown that M45 mutant viruses fail to infect mice [137,138] due to excessive activation of necroptosis [50,134]. In DAI/ZBP1-induced necroptosis, DAI/ZBP1senses viral RNA sensor [139] instead of DNA as previously thought [140]. It is shown that RIPK1 knockdown or inhibition fails to protect from MCMV-induced necroptosis, whereas inhibition of the viral transcriptional activator, immediate-early viral trans-activator (IE3) protected from MCMV-induced necroptosis [141].…”
Section: Dna Viruses Mediated Anti-necroptosismentioning
confidence: 99%
“…It is shown that M45 mutant viruses fail to infect mice [137,138] due to excessive activation of necroptosis [50,134]. In DAI/ZBP1-induced necroptosis, DAI/ZBP1senses viral RNA sensor [139] instead of DNA as previously thought [140]. It is shown that RIPK1 knockdown or inhibition fails to protect from MCMV-induced necroptosis, whereas inhibition of the viral transcriptional activator, immediate-early viral trans-activator (IE3) protected from MCMV-induced necroptosis [141].…”
Section: Dna Viruses Mediated Anti-necroptosismentioning
confidence: 99%
“…MCMV encodes M45 that disrupts the ZBP1‐RIPK3 interaction and blocks necroptosis activation upon MCMV infection (Figure 3B ). Using a mutated MCMV in M45 (MCMV‐M45 mutRHIM ), ZBP1‐mediated necroptosis is activated upon infection and, more importantly, this activation is induced by the newly transcribed RNA generated upon infection, which binds to the two Zα domains of ZBP1 [ 60 , 61 , 70 ]. Herpes simplex virus 1 (HSV1) triggers necroptosis via ZBP1, encoding ICP6 as the antagonism, with a mechanism reminiscent of MCMV [ 71 ] (Figure 3B ).…”
Section: Introductionmentioning
confidence: 99%
“…Much evidence shows that the Z-DNA of alternative pyrimidine purine (APP) sequences really exists in vivo and is associated with diverse diseases [3][4][5][6][7]. It has been shown that Z-DNA is involved in regulating gene expression, inducing chromosome recombination, and so on [8][9][10][11][12][13][14][15][16]. However, Z-DNA is hard to form without topological constraint or special conditions such as chemical modification or high salt concentrations because it is easily transferred to B-DNA.…”
Section: Introductionmentioning
confidence: 99%